Effects of upper body strength training using elastic band on shoulder isokinetic strength in elite rowers - Kasmi, S.; Hammami, A.; Aloui, A.; Khlifa,R.; Gaied, S. (The Swedish Journal of Scientific Research, 2019)
Imbalance and weakness in shoulder rotator muscles has been considered a risk factor for injuries in athletes. The purpose of this study was to investigate the effects of strength training on external and internal shoulder rotator muscle strength using elastic band compared with habitual training using weight machines in elite rowers. Fourteen elite rowers (M ± SD: age 18±2 years, height 179.4±4.6 cm, weight 70.5±6.3 kg, and Body fat 10.7±2.5 %) were tested for concentric internal (IR) and external rotation (ER) peak torque (PT), and acceleration time (ACC) before and after 12 weeks of strength training using habitual weight machines or elastic band. The results demonstrated that the 2 training modalities significantly improved PT and only elastic band training decreases ACC for both IR and ER in the right and left shoulder (all p < 0.001). Between-group differences in change revealed that training using weight machines was significantly superior (39 to 49%; all P < 0.01; large effects) for PT improvement. However, elastic band training was superior (40 to 100%; P < 0.02; large effects) on decreasing ACC. Training using weight machines was superior for improving shoulder PT compared with elastic band. However, the latter training was more effective in reducing ACC and therefore is recommended especially in injury preventive and rehabilitation-based strength training.